THE IMPLEMENTATION OF CONTENT-BASED INSTRUCTION IN ISLAMIC HIGHER EDUCATION - Shofiya, Arina (Jurnal Bahasa Lingua Scientia, 2019)
Together with the development of technology and knowledge in English Language Teaching, teaching model develops variously. There is no single model of teaching meets all the students? needs, especially in Islamic higher education institution. Content-Based Instruction (CBI) offers a teaching model which integrates the teaching of subject matters and language skills in a class. The findings of the present research reveal the benefits of the implementation of CBI cover cognitive and affective aspect. The knowledge of the Islamic contents and foreign languages increases and the behavior gets better. However, the more substantial finding is that the implementation of CBI eases the burden of the lecturers in doing two main tasks, namely, teaching (internalizing) Islamic values and teaching language skills.